Pengaruh Efek Sisa Kombinasi Biochar Sekam Padi Dan Dolomit Terhadap Pencucian Unsur N Pada Budidaya Tanaman Jagung (Zea Mays L.) - Ilahi, Ranti Prima; Sefano, Muhammad Aknil (Journal Arunasita, 2025)
Inceptisol is a type of soil that has a dominant coarse fraction. Inceptisol has a productivity that is generally still low because it has a coarse texture with low-moderate soil organic matter content, which has a negative impact on soil physical properties and plant growth. This study aims to examine the long-term effect of biochar on N element leaching through the residual effects of rice husk and dolomite biochar. The method used in this study was a Completely Randomized Design with 8 experiments with 3 replications, so that 24 experimental units were obtained. Based on the results of the study, it can be concluded that inceptisol soil if given Biochar + dolomite treatment, makes the soil too porous and causes high N nutrient leaching. giving biochar up to 22 tons + 1.5 tons of dolomite (treatment H) is able to maintain the pH of water from acidic rain.